Youth Access to Tobacco in Violation of Sales Restrictions: Evidence from the Nigerian Global Youth Tobacco Survey (GYTS) (Nigerian Dental Journal, 2026)
Background: Despite Nigeria’s early commitment to the WHO Framework Convention on Tobacco Control (FCTC), enforcement of Article 16, which prohibits the sale of tobacco to minors remains poorly documented. Since no Global Youth Tobacco Survey (GYTS) has been conducted in Nigeria since 2008, there is a critical evidence gap on how adolescents continue to access tobacco products in violation of legal restrictions. This study provides the first detailed assessment of illegal youth access to tobacco, examining associated demographic, behavioral, and policy awareness factors using nationally representative microdata.Methods: We analyzed the Nigeria GYTS 2008, a cross-sectional school-based survey employing a two-stage cluster sample design across five sentinel areas (Abuja, Cross River, Ibadan, Kano, Lagos). The analytic sample included 2,379 adolescents aged 13–15 years. Complex survey design corrections were applied using Primary Sampling Units (PSU) strata, and final sample weights. The outcome variable—illegal access to tobacco—was defined as purchasing cigarettes without refusal due to age in the past 30 days. Weighted descriptive analyses, chi-square tests, and survey-adjusted logistic regressions (Models 1–3) were performed to identify predictors, including sex, age, rural residence, parental and peer smoking, school type, and awareness of youth-sales laws.Results: Overall, 13.2% (95% CI: 11.6–14.8) of Nigerian adolescents reported successful purchase of cigarettes without being refused for age. Rural youth had higher illegal access (18.5% vs. 11.4%, p
Keywords: GYTS.; FCTC Article 16; Nigeria; Policy enforcement; Sales restrictions; Adolescent tobacco access